An introduction to software defined networking (SDN) - Slattery, Terrry (LiveLessons., 2014)
"This video course provides an introduction to the OpenFlow-based version of SDN, providing the fundamental knowledge to effectively communicate with vendors who are selling products labeled as SDN."--Resource description page.